On hyers-ulam stability of nonlinear second order ordinary and functional differential equations (2018)
In this paper, we consider the Hyers-Ulam stability of some nonlinear second order ordinary and functional differential equations. As mathematical technique, we use some nonlinear extension of the Gronwall integral inequality.